2006
DOI: 10.1136/sti.2006.020768
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the prevalence of sexually transmitted infections and genital symptoms in an urban setting in southern India

Abstract: Given a high prevalence of HSV2 in the study population, interventions targeting HSV2 transmission may be particularly relevant for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 28 publications
4
33
1
Order By: Relevance
“…The prevalence of C. trachomatis infection was similar to a population-based study of 1014 postpartum women in a rural district of south eastern Nepal [9] and to that reported from India (0.4%) [17]. However, it was substantially lower than among women in rural areas in China (2.1%) [18] and that estimated for Southeast Asia (1.8%) [1].…”
Section: Discussionsupporting
confidence: 78%
“…The prevalence of C. trachomatis infection was similar to a population-based study of 1014 postpartum women in a rural district of south eastern Nepal [9] and to that reported from India (0.4%) [17]. However, it was substantially lower than among women in rural areas in China (2.1%) [18] and that estimated for Southeast Asia (1.8%) [1].…”
Section: Discussionsupporting
confidence: 78%
“…12 In a community-based study in Southern India, a prevalence of STIs of 15.6% was reported. 13 The slightly higher prevalence in our study could be because the present study was hospital based. The most common syndrome in this study was vaginal discharge (12.0% of subjects) followed by urethral discharge (4.6% of subjects).…”
Section: Discussionmentioning
confidence: 51%
“…19 It has also been found that most of the self-reported genital symptoms could not be linked to a laboratory-detected STI. 13,20 Nevertheless, in this study, the inability to establish a laboratory diagnosis of chlamydia, chancroid, herpes and lymphogranuloma infections could have contributed to the lower microbiological prevalence. This further highlights the usefulness of syndromic diagnosis where laboratory facilities are grossly inadequate.…”
Section: Discussionmentioning
confidence: 78%
“…27 The wives of those who used condoms only sometimes depending upon their partners, are vulnerable for acquisition of STI/HIV from their spouses.…”
Section: Use Of Condommentioning
confidence: 99%